Pengembangan Multimedia Interaktif IPA di Kelas V SD Pokok Bahasan Organ Tubuh Manusia dan Hewan - Octario Sakti Susilo; I Nyoman Sudana Degeng; Susilaningsih (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2017)
The purpose of this study is to develop valid interactive multimedia as a learning medium for fifth-grade science subjects on the topic of human and animal body organs, so that the learning process becomes more engaging and increases students’ motivation to learn. Data were collected using questionnaires from one media expert, one material expert, and 20 students, and analyzed using qualitative and quantitative techniques. The results of this study show that the multimedia is declared valid for use based on the calculation results from the questionnaires of the media expert, material expert, small-group student trials, and large-group student trials.